PEMERIKSAAN KADAR MERKURI DAN KELUHAN KESEHATAN DALAM DARAH WANITA PEMAKAI KRIM PEMUTIH DENGAN METODA INDUCTIVELY COUPLED PLASMA - Mayaserli, Dyna Putri; Sasmita, Weni (IAIN Batusangkar, 2016)
Whitening cream is a mixture of chemicals or other materials that serve to lighten skin or fade black spots on the skin. Bleaching creams that contain mercury is very harmful for health. The purpose of this study is to examine and establish the levels of mercury in the blood of women users of whitening creams in the city of Padang. Blood samples examined as many as 10 samples and whitening creams as much as 5 samples. The qualitative analysis of the bleaching creams done with color test method, while the quantitative analysis of the blood samples used method ICP (Inductively Coupled Plasma). The results showed that of the five samples examined bleaching creams with color test, there are three positive samples contain mercury. while the results showed that the ten blood samples studied one sample contained mercury levels in the blood exceeds the normal value is 0.04435 mg / L. The use of whitening creams containing mercury can cause a variety of health complaints, ranging from skin discoloration, which in turn can cause black spots on the skin, allergies, skin irritation as well as the use of high doses can cause permanent brain damage, and can cause cancer.